La invención del Indio americano y su imagen: cuatro arquetipos entre la percepción y la acción política - Jesús Bustamante (Centre de Recherches sur les Mondes Américains, 2017)
Visual image was of crucial importance when perceiving and giving meaning to the native populations of those lands to which Europe was arriving, both in its first (15th and 16th Centuries) and second expansión (17th to 18th Centuries). This paper aims to show how visual media have a logic, possibilities and limitations that are specific to them, and that have had significant influence on the West’s prevailing image of those indigenous peoples. The object of this paper is to show the existence and characteristics of four great visual archetypes about the American Indian, beginning in the 16th Century and reaching our days. Four achetypes thar are not incompatible with each other, even though they have very different social and political implications.